ART TEACHING IN PRIMARY CLASS - Salimova Ganjina Salomovna (Web of Journals Publishing, 2025)
This article is based on a review of artistic teaching mechanisms based on the didactic game approach using the example of one subject.
Keywords: Didactic game, mechanism, play, critical thinking, positive thinking, improvement.